Water column raw data (Kongsberg EM712 entire dataset) of RV MARIA S. MERIAN during cruise MSM132 - Christian Berndt; Morelia Urlaub; Paraskevi Nomikou; Mia Schumacher; Anne-Cathrin Wölfl (PANGAEA, 2025)
Raw water column data were collected aboard RV MARIA S. MERIAN during cruise MSM132 using a 40-100kHz Kongsberg EM 712 multibeam echosounder. The expedition took place during 2024-12-03 – 2025-01-02 from Catania (Italy) to Heraklion (Greece) in the Mediterranean Sea. The aim of M132 (MULTI_MAREX) is to develop new monitoring technology towards an early warning system for natural hazards in the Aegean Sea. The cruise was supposed to set the scene by acquiring geophysical and video data to fill crucial gaps in the current understanding of the region and to provide a baseline for assessing geological change. Data were recorded within the EEZ of Greece. 24 files within this dataset (0000_20241205_212238_MSM_EM712.all - 0023_20241206_071221_MSM_EM712.all) contain lines used for system calibration. Following the calibration procedure, calibration coefficients were computed and then corrected. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Project Underway Research Data and published according to the FAIR principles.